Brunauer-Emmett-Teller, Fourier-transform infrared, and scanning-electron-microscope analysis of biochar from marine organic waste - Benny Hidayat; Nur Ulina Warnisyah Sebayang; Jamilah Jamilah; Adhira Mahardika (Universitas Sebelas Maret, 2025)
Brunauer Emmet Teller (BET), Fourier Transform Infrared (FTIR), and Scanning Electron Microscope (SEM) study are important methods for characterizing biochar produced from marine organic waste. Each technique provides insights into the physical and chemical structure of biochar, which are essential for understanding its properties and potential as a soil amendment. The purpose of characterizing biochar from marine organic waste by BET method is to specify the superficies point, pore size, and total pore volume of the biochar, FTIR to identify the characterization of organic compounds, and SEM to understand the microstructure of the biochar. BET test results indicate that biochar from marine organic waste has a superficies point of 6.213m²g-1, a pore size of 21.690Å, and Barrett–Joyner–Halenda (BJH) adsorption and desorption pore volumes of 0.040cc g-1 and 0.035cc g-1, respectively. This biochar demonstrates a higher adsorption capacity. FTIR tests reveal that the functional groups and chemical content of the biochar from marine organic waste include six types of vibrations with different wavenumbers and % transmittance values. SEM analysis at various magnifications shows that the biochar from marine organic waste (MOW) has a complex pore structure. The characterization of biochar derived from MOW illustrates its potential as a cost-effective soil amendment and environmental remediation material. Its microstructure suggests long-term stability in soil, supporting carbon sequestration and improved soil health.